Concomitant Haemophilus influenzae infection and anti-N-Methyl-D-Aspartate receptor encephalitis in a 7-year-old previously healthy girl: a case report - Abdul Rahman, Nurul Aimi; Mahayidin, Hasni; Tuan Soh, Tuan Suhaila; Ibrahim, Rosni (UPM Press, 2022)
Encephalitis is the inflammation of the brain which is usually caused by viral infections, but it can be also due to other non-infectious agents. We report an interesting case of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis with Haemophilus influenzae co-infection in association with severe acute respiratory syndrome coronavirus 2, without pulmonary involvement or fever.